Lymphoma occurring in patients with cutaneous melanoma. Issue 9 (29th July 2010) - Verwer, Nick; Murali, Rajmohan; Winstanley, Julie; Cooper, Wendy A; Stretch, Jonathan R; Thompson, John F; Scolyer, Richard A
Abstract : Background: Non-melanoma malignancies are not uncommon in patients with melanoma. This study sought to determine the incidence of lymphoma in patients with melanoma compared with the general population, and to characterise their clinical and pathological features. Methods: Patients diagnosed with melanoma and lymphoma between January 1992 and December 2007 were identified from the databases of Melanoma Institute Australia (MIA) and the Department of Tissue Pathology and Diagnostic Oncology, Royal Prince Alfred Hospital (RPAH). The clinical histories of the patients in the MIA database and pathology reports in the RPAH archives were reviewed. The incidence risk for melanoma and non-Hodgkin lymphoma was obtained from Australian Cancer Incidence and Mortality registry data. Results: Of 18 226 patients with melanoma, 55 (0.3%) had lymphoma. Lymphoma was diagnosed subsequent to melanoma in 23 (41.8%) patients, prior to melanoma in 7 (12.7%) patients, and concurrently with melanoma in 25 (45.5%) patients. 53 (96.4%) patients developed non-Hodgkin lymphoma (NHL), the most common subtypes being chronic lymphocytic leukaemia/small lymphocytic lymphoma (49.1%), follicular lymphoma (23.6%) and diffuse large B-cell lymphoma (16.4%). Two (3.6%) patients developed Hodgkin lymphoma. Melanoma patients had a significantly higher risk of developing NHL than the general population (standardised incidence rate 3.5). Conclusions: A small but significant proportion of patients with melanoma develop lymphoma, either synchronously or metachronously. Lymph node specimens from melanoma patients might harbour lymphoma, and might represent the first recognised site of disease. A high index of suspicion for lymphoma when evaluating lymph nodes from patients with melanoma will ensure prompt diagnosis and appropriate management.